PERSEPSI REMAJA PEROKOK AKTIF DI KAMPUNG BENDUL MERISI SURABAYA TENTANG PERINGATAN BAHAYA MEROKOK PADA MEDIA IKLAN PAPAN REKLAME - Rini Ganefwati; Ita Nurlita; Andi Wahyudi (INTELEKTUAL ( E-Journal Administrasi Publik dan Ilmu Komunikasi ), 2023)
The perception of active smoking adolescents in Kampung Bendul Merisi Surabaya towards warnings about the dangers of smoking on billboard advertising media is a study that reminds about the dangers of smoking for active smokers, especially teenagers. The objects in this study were active smoking teenagers in Bendul Merisi Village, Surabaya. This type of research is a qualitative descriptive research. Data collection methods used in this study are observation, in-depth interviews and documentation. Sources of research data are primary data and secondary data. The data analysis includes, data reduction, data presentation, and drawing conclusions. In this study there were 7 informants who were active smokers. The results of this study indicate that some adolescent smokers are aware of the warning labels listed on billboard advertising media, but they still want to carry out their habit, namely smoking, even though they know the warnings about the dangers of smoking in the advertising media and cigarette packs. assume that the warnings about the dangers of smoking contained in billboard advertising media are commonplace and do not have any impact on them. Even though they know the effects of smoking, they still do their habit, namely smoking. Because smoking has become a habit for them which is difficult to leave.